ODONTALGIA DAN PENATALAKSANAANNYA DI DALAM MULUT - Satria Boedi (Faculty of Dentistry, Universitas Indonesia, 2015)
Dental pulsating pain such as pulpitis occurring without a clear etiology often complicates dentists in treating their patients. The dental pulsating pain without symptoms is known as odontalgia pain, an orofacia pain distributed to the oral region by every trigeminal nerve involved, making it difficult to diagnoses, causing uncomforatble experince for the patient. Odontalgia pain symptoms ucually occur in teeth with pulpal defects, periapical involvements, erupting third molars, dental trauma. They are often confused with symptoms occurring in oral herpes zoster, leukemia and diabetes mellitus. Through exploration of every possible etiologies for odontalgia pain, it is hoped that dentists could prevent tissue damage and undesirable complication.